PENGEMBALIAN STATUS HUKUM TANAH ULAYAT ATAS HAK GUNA USAHA - Jasmir, Jasmir (Kopertis Wilayah X, 2018)
Land tenure by the state does not mean possessed, but as the name of the land, grants only the right of access to land which can be given to the land, its designation, use and maintenance and its arrangement to the law and the relations it can do to those lands. Article 3 of the BAL is indeed available the term